Diurnal Variation in the Occurrence of Stroke and its Relation with Diabetes Mellitus - Hoque, Mirza Azizul; Islam, Shahidul; Islam, Md Sirajul; Alam, Md Billal; Arif, SM; Rahim, Abdur; Ur-Rahman, Ashraf (Journal of Medicine, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Objective- To observe diurnal variation in stroke onset and its relation to diabetes mellitus. Methods - A consecutive series of 139 patients with stroke was admitted at a reference hospitals; the time of onset of symptoms were noted. We compared the diurnal variations between stroke onset both in the diabetic and non-diabetic subjects. Results - Time of occurrence of stroke was highest in the second quadrant of the 24 hour clock and lowest in the first quadrant. There was no significant association between time of occurrence of stroke and diabetes mellitus Conclusions - Our study contributes further evidence for a susceptibility stroke event between 6 AM and noon and gives further insights into the possible mechanisms leading to cerebrovascular ischemia. This study also concludes that there is no association between diurnal variation in the occurrence of stroke and diabetes mellitus. Key Words: diurnal variation, stroke onset Â DOI = 10.3329/jom.v9i2.1434 J MEDICINE 2008; 9 : 75-77